Spinopelvic Dissociation: Comparison of Outcomes of Percutaneous versus Open Fixation Strategies - Jeffrey M. Pearson; Thomas E. Niemeier; Gerald McGwin; Sakthivel Rajaram Manoharan (Advances in Orthopedics)
Introduction. Spinopelvic dissociation injuries are historically treated with open reduction with or without decompressive laminectomy. Recent technological advances have allowed for percutaneous fixation with indirect reduction. Herein, we evaluate outcomes and complications between patients treated with open reduction versus percutaneous spinopelvic fixation. Methods. Retrospective review of patients undergoing spinopelvic fixation from a single, level one trauma center from 2012 to 2017. Patient information regarding demographics, associated injuries, and treatment outcome measures was recorded and analyzed. All fractures were classified via the AO Spine classification system. Results. Thirty-one spinopelvic dissociations were identified: 15 treated with open and 16 with percutaneous techniques. The two treatment groups had similar preoperative characteristics including spinopelvic parameters (pelvic incidence and lumbar lordosis). Compared to open reduction internal fixation, percutaneous fixation of spinopelvic dissociation resulted in statistically significantly lower blood loss (171 cc versus 538 cc; p=0.0013). There were no significant differences in surgical site infections (p=0.48) or operating room time (p=0.66). Conclusion. Percutaneous fixation of spinopelvic dissociation is associated with significantly less blood loss. Treatment outcomes in terms of infection, length of stay, operative cost, and final alignment between the open and percutaneous group were similar.